Proceedings of the 1st International Conference on Advanced Multidisciplinary Research (ICAMR 2018) 2019
DOI: 10.2991/icamr-18.2019.92
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Motoric Ability of Class I Elementary School Students in Makassar City

Abstract: This study aims to determine the level of students motoric abilities of class 1 at Bawakaraeng 1 Elementary School, Makassar City. This study is a quantitative descriptive study. The subjects of this study were all class 1 students of Bawakaraeng 1 Elementary School, Makassar City, with a total number of 68 children divided into 2 (two) classes namely class IA and class IB. The data collection technique uses tests to measure motoric abilities, which consist of 5 test items, namely running back and forth, runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The research found that students' motor level in physical education FKIP Universitas Islam Riau included medium. Several things that influence someone's motor ability level are environment stimulus, nutrition status, gender, mature step, heredity, and genetic (Wahyudi, Saharullah, & Muhammadong, 2018).…”
Section: Frequencymentioning
confidence: 99%
“…The research found that students' motor level in physical education FKIP Universitas Islam Riau included medium. Several things that influence someone's motor ability level are environment stimulus, nutrition status, gender, mature step, heredity, and genetic (Wahyudi, Saharullah, & Muhammadong, 2018).…”
Section: Frequencymentioning
confidence: 99%